Principiile de descriere bibliografică: ce s-a schimbat? dr. conf. univ. Natalia Goian - admin, admin (BIBLIOPOLIS, 2022)
The importance of bibliographic description is undeniable. After as argued in the Unified Edition, approved by the Committee Standing IFLA Cataloging Section, Description International Standard Bibliography (ISBD) is intended to serve as the main standard for promoting control universal bibliographic, ie to make available universally and quickly, in an internationally acceptable form, bibliographic data for all resources published in all countries. The main goal of this publication is to familiarize librarians with the changes produced in recent years in the field of cataloging.